The Impact of 1 Million Ha Rice Fields Program on Rice Production and Farmers’ Welfare - Dahiri, Dahiri (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2018)
Data on the area of national rice fields and rice production showed an increasing trend, but the welfare of farmers also declined. The purpose of this research is first to calculate the impact of rice field area and productivity on rice production; second, to calculate the influence of wetland area, productivity, and price on farmers' welfare; and third, to count the effectiveness of paddy production and the program of 1 million ha of new fields. The method used is a regression with natural logarithms and data from 33 provinces in Indonesia in 2013–2016. The result of the data analysis showed that first wetland area and productivity have a positive and significant effect on production; both wetland area, productivity, and price have a positive effect on farmer welfare, but only significant land area; the effectiveness of paddy production is in the quite effective category; and program effectiveness, which produces 1 million ha of new fields, is in the ineffective category.